The touch of civilization : comparing American and Russian internal colonization - Sabol, Steven (University Press of Colorado, 2016)
This work compares the process and practice of nineteenth-century American and Russian internal colonization, a form of contiguous, continental expansion, imperialism and colonialism that incorporated Indigenous lands and peoples. It provides a critical, comparative examination of internal colonization exercised by the United States and Russia and experienced by two Indigenous populations, the Sioux and the Kazakhs. In particular, it examines how and why perceptions of the Sioux and Kazakhs as ostensibly uncivilized peoples, and similarly held American and Russian perceptions of the Northern Plains and the Kazakh Steppe as "uninhabited" regions that ought to be settled, reinforced American and Russian government sedentarization policies and land allotment programs among the Sioux and Kazakhs. In addition, it compares the processes practiced by the two empires and the various forms of Sioux and Kazakh martial, political, social and culture resistance evident throughout the 19th century